New Science Curriculum Based on Inquiry Based Learning - A Model of Modern Educational System in Republic of Macedonia - Natalija Aceska (Journal of Education in Science, Environment and Health)
The process of globalization, more progressive development of the scientific findings, new technology and the way of communicating with the new forms of literacy in which the most secure spot has been taken by the development of natural sciences in the spirit of sustainable development have been the reasons that make science and sustainable development an educational imperative. The development of natural sciences in the educational processes in Republic of Macedonia has become an essential process which is being permanently improved with the goal to find the best solutions for its improvement. Currently, all of the elementary grade teachers have to face this process. One of the most recent changes is the study of natural sciences according to the adapted educational curriculum from the Cambridge International Examination Center. The goal of this reform is to lead the students on the right way of becoming future “scientists”. The programs include research that encourages students to ask questions and derive the answers themselves with the support from their teachers. This is a proven method with which natural science classes will become more interesting for the students and the findings will remain learned. The educational curriculum also allows the students to develop their critical thinking and to think and use the proofs. Students will easily learn that natural sciences are important and can help them in solving everyday life’s problems according to the principles of education for sustainable development. A very important part in the adaptation and realization of the adapted educational curriculum from the Cambridge International Examination Center is being played by the information and communication technology (ICT) that is a very useful resource for the development of the knowledge, skills and understanding among students. ICT needs to improve the quality of the teaching. The teachers will have the opportunity to choose and use the most appropriate and effective ICT resources.